Causality and Motivation. - Poli, Roberto (Philosophische Analyse / Philosophical Analysis., 2010)
The belief is widely held that the physical world is causally-driven. The world is one because a tangled web of causally-driven processes keeps it together. However, both the psychological and the social worlds cannot be articulated in causal terms only. Hereby, "motivation" is used as the most general term referring to whatever keeps (synchronically) together and provides (diachronic) reasons explaining the behavior of psychological and social systems. In order to systematically address these problems, a categorical framework is needed for understanding the various types of realities populati.